1993
DOI: 10.1021/bi00211a008
|View full text |Cite
|
Sign up to set email alerts
|

Affinity labeling of glutathione S-transferase, isozyme 4-4, by 4-(fluorosulfonyl)benzoic acid reveals Tyr115 to be an important determinant of xenobiotic substrate specificity

Abstract: Incubation of 4-(fluorosulfonyl)benzoic acid (4-FSB), a xenobiotic substrate analogue, with the 4-4 isozyme of rat liver glutathione S-transferase at pH 7.5 and 25 degrees C results in a time-dependent inactivation of the enzyme. The rate of inactivation exhibits a nonlinear dependence on 4-FSB concentration from 0.50 to 7.85 mM, with kmax = 0.082 min-1 and a KI of 1.95 mM. Nearly 1 mol of reagent/mol of enzyme subunit is incorporated when the enzyme is maximally inactivated. Protection against incorporation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 24 publications
4
24
0
1
Order By: Relevance
“…The activity toward EA was detected in freshly isolated hepatocytes and did not increase with time and elevated GSTP1 expression, suggesting that other GST family members may also catalyze this reaction. Other reports have also suggested that alpha- (Stenberg et al, 1992), mu- (Barycki and Colman, 1993), and theta- (Hiratsuka et al, 1990) class GSTs contribute to EA conjugation in rat. However, Henderson et al (1998) reported that EA metabolism is lost in the liver of the GSTP knockout mouse.…”
Section: Discussionmentioning
confidence: 87%
“…The activity toward EA was detected in freshly isolated hepatocytes and did not increase with time and elevated GSTP1 expression, suggesting that other GST family members may also catalyze this reaction. Other reports have also suggested that alpha- (Stenberg et al, 1992), mu- (Barycki and Colman, 1993), and theta- (Hiratsuka et al, 1990) class GSTs contribute to EA conjugation in rat. However, Henderson et al (1998) reported that EA metabolism is lost in the liver of the GSTP knockout mouse.…”
Section: Discussionmentioning
confidence: 87%
“…The enzyme-catalyzed formation of the conjugate between 600 M glutathione and 100 M mBBr was measured in 0.1 M potassium phosphate buffer, pH 6.5, at 25°C using the method of Hulbert and Yakubu (32) with a Perkin-Elmer MPF-3 fluorescence spectrophotometer (excitation at 395 nm and emission at 480 nm). ) (34). Corrections for the nonenzymatic reactions were made for all assays.…”
Section: Materials-frozenmentioning
confidence: 99%
“…Affinity labeling studies using S-(4-bromo-2,3-dioxobutyl)glutathione and 4-(fluorosulfonyl)benzoic acid demonstrated that Tyr 115 in both isozyme 3-3 and 4 -4 is located in the xenobiotic binding site and contributes to binding of these hydrophobic substrates in addition to its function as a general acid in reactions with certain substrates (i.e. those involving epoxide ring opening and Michael addition reactions) (11,16,17). More recently, Tyr 115 has been identified as a target of other affinity labels (18,19).…”
mentioning
confidence: 99%